Its got me stumped...

3logx - log(x-1) + log(x+1)

Printable View

- November 25th 2008, 07:05 PMHosedWrite as a single logarithm...
Its got me stumped...

3logx - log(x-1) + log(x+1) - November 25th 2008, 07:18 PMDavid24
hey mate,

there are three log laws that need to be employed in order to simplify your expression,

(1) nlogA = logA^n

(2) log(A) + log(B) = log(AB)

(3) log(A) - log(B) = log(A/B)

3logx - log(x-1) + log(x+1) = logx^3 - log(x-1) + log(x + 1)

= log(x^3/(x-1)) + log(x+1)

= log((x^3/(x-1))*(x+1))

or

= log(x^3(x+1)/(x-1))

Hope this helps,

Regards,

David - November 26th 2008, 05:57 AMmohamedsafygood
(Clapping)

that was helpful david